Identifying areas for field conservation of forages in Latin American disturbed environments - Peters, Michael; Hyman, Glenn G.; Jones, Peter G. (2005)
This paper uses the spatial analysis tools DIVA and FloraMap to identify potential areas for the in situ conservation of a set of 10 forage species. We introduce the idea of roadside verges as conservation areas and discuss the risks and opportunities of two potential scenarios for conservation. These are the introduction of mass reservoirs outside of the original areas of collection and conservation inside the area of origin. Four potential areas for in situ conservation in Latin America are identified. Although more detailed studies using remote sensing, soil information, and field reconnaissance will be necessary for a final assessment of the suggested areas as field conservation sites, we discuss the possibilities of establishing low-maintenance communities and the potential dangers of introducing harmful weed species. We do not have final answers with regard to the permanent maintenance of genetic diversity in these areas but suggest that further studies of genetic drift in the populations would not only be scientifically useful but might also lead to identifying useful genotypes for local use.